Application of biogeographical data of frogs to prioritize conservation areas in Borneo - Kueh, Boon-Hee; Maryati, Mohamed; Das, I.; Chew, Danny TW (2002)
Prioritization of conservation areas is an important aspect of conservation biology to enhance biodiversity conservation. WillI the increase in threats to biodiversity and environment, prioritization of conservation. areas has become crucial as it reviews areas with the best representation of biodiversity so that conservation efforts can be targeted. Feasibility and effectiveness of conservation translate to saving of time, money, personnel and most importantly, the limited natural resources. Prioritization of conservation areas requires four components: analytical tool, biodiversity value, selected organism and selected site.